(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
This article aims to think about a particular type of contemporary image: the Internet meme. As a part of our visual economy, it is intended to expose its impact as well as its genealogy to understand why memes are so popular and efficient nowadays. This piece focuses on political memes, belonging to a satirical tradition of images, implying that these so-called “poor” images are not a totally new phenomenon but, on the contrary, a continuity with preceding visual artifacts.